Autorzy:Aleksandra Ciszkowska, Alina Przychoda, Zygmunt Łaszczyk
Wydawnictwo:WSiP
Rok wydania:2012
Jeśli wiesz, że a=(2√7-1)*(-4)+(√7+3)*8-5 3/44.57 gwiazdek na podstawie 7 opinii

Jeśli wiesz, że a=(2√7-1)*(-4)+(√7+3)*8-5 3/4

34Zadanie
35Zadanie
36Zadanie
37Zadanie
38Zadanie
39Zadanie

`a=(2sqrt7-1)*(-4)+(sqrt7+3)*8-5 3/4= -8sqrt7+4+8sqrt7+24-5 3/4=` 

`=28-5 3/4=22 1/4`  

`b=(6(sqrt5-4sqrt2)+(3sqrt2-1,5sqrt5)*(-4))/(72sqrt2-24sqrt5)=` `(6sqrt5-24sqrt2+(-12sqrt2)+6sqrt5)/(72sqrt2-24sqrt5)=` 

`=(12sqrt5-36sqrt2)/(72sqrt2-24sqrt5)=(strike12(sqrt5-3sqrt2))/(strike12(6sqrt2-2sqrt5))=`    `(sqrt5-3sqrt2)/(6sqrt2-2sqrt5)*(6sqrt2+2sqrt5)/(6sqrt2+2sqrt5) stackrel( \ \ \ \ \ \ (a+b)(a-b)=a^2-b^2 \ \ \ \ \ )=`  

`=(6sqrt10+10-36-6sqrt10)/(72-20)=(-26)/52=-1/2`   

 

 

 

a)

`(2ab)/(a-b)=(2*22 1/4*(-1/2))/(22 1/4-(-1/2))=` `((-1)*22 1/4)/(22 1/4+2/4)=(-22 1/4)/(22 3/4)= ` `(-89/(strike4))/(91/(strike4))` `=ul(ul(-89/91))` 

b)

`1/b-(2(a-b))/(3a)=` `1/(-1/2)-(22 1/4-(-1/2))/(3*22 1/4)=` ` `  `(-2)- (22 1/4+2/4)/(66 3/4)=` `(-2) - (22 3/4)/(66 3/4)=`

`=(-2) - (91/(strike4))/(267/(strike4))=(-2)- 91/267=ul(ul(-2 91/267))`

c)

`(a+b)/(a/89)-(3b+25)/(5b^2)=(89(a+b))/a-(3b+25)/(5b^2)` `= (89(-1/2+22 1/4))/(22 1/4) - (3*(-1/2)+25)/(5*(-1/2)^2)=` 

`=(89(-2/4+22 1/4))/(22 1/4) - (-3/2+25)/(5* 1/4)=` `(89(21 3/4))/(22 1/4) - (23 1/2)/(5/4)` `=(strike89*87/strike4)/(strike89/strike4)-(47/2)/(5/4)=`   

` ` `87- 47/(strike2^1) *strike4^2/5=87-94/5` `=87- 18 4/5=ul(ul( 68 1/5))`